1994
DOI: 10.1002/eji.1830240831
|View full text |Cite
|
Sign up to set email alerts
|

Ineffective expression of CD40 ligand on cord blood T cells may contribute to poor immunoglobulin production in the newborn

Abstract: A major feature of the immature immune system in the newborn is its inability to produce significant levels of immunoglobulins other than IgM in response to antigens. It has recently been demonstrated that interaction of the CD40 molecule on B cells with the CD40 ligand (CD40L) on activated T cells is pivotal for immunoglobulin switching. In view of these findings, we have tested cord blood mononuclear cells (CBMC) for expression of CD40L. Our data clearly demonstrate that freshly isolated CBMC do not express … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 32 publications
1
38
1
1
Order By: Relevance
“…It is generally regarded as an activation marker (28). However, we and others (1,27,29,30) did not find other markers of activation in neonatal cord or infant blood, such as increased expression of CD25, HLA-DR, CD69, and CD154 (CD40 ligand). Nor did we find an increase of thymocyte-like CD1a ϩ or CD4 ϩ /CD8 ϩ double-positive T cells.…”
Section: Discussioncontrasting
confidence: 61%
“…It is generally regarded as an activation marker (28). However, we and others (1,27,29,30) did not find other markers of activation in neonatal cord or infant blood, such as increased expression of CD25, HLA-DR, CD69, and CD154 (CD40 ligand). Nor did we find an increase of thymocyte-like CD1a ϩ or CD4 ϩ /CD8 ϩ double-positive T cells.…”
Section: Discussioncontrasting
confidence: 61%
“…Are the cells functionally mature but have no antigenic exposure? Previous findings implicate low or absent CD40L expression on T cells as one of the key factors, since CD40-CD40L interactions are necessary for both B-cell activation and isotype switching [6]. It has also been shown that cord blood T cells are poor producers of certain cytokines which play a major role in isotype switching [19].…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a reduced incidence and severity of acute or extensive chronic graft-vs-host disease (GVHD) in CB transplantation (CBT) when compared with results obtained using PB and BM (22)(23)(24). Accumulating results suggest that reduced incidence and severity of GVHD in CBT may involve an inactivation of donor-derived CB T cells with respect to the secretion of proinflammatory cytokines as well as killing activity due to the expressions of perforin and Fas ligand (17,(25)(26)(27)(28). Clinical manifestations suggested that transplanted T cells derived from BM and PB inoculum may be activated, while transplanted CB T cells may exhibit inactivated status following stimulation with allogeneic Ag and various cytokines (17,(22)(23)(24)29).…”
Section: Mip-1␣ and Rantes As Compared With That Of Cd45romentioning
confidence: 99%